Growth of microalgae Scenedesmus sp in ethanol vinasse - Ramirez,Nelzy Neyza Vargas (2014)
This study evaluated the feasibility of using vinasse as a nutrient source for microalgae cultivation. The Scenedesmus sp was grown in a medium supplemented with vinasse and process variables were optimized using a factorial design and a Central Composite Design (CCD). The factorial design results showed that it was possible to cultivate microalgae at concentrations of up to 40% of vinasse in the culture medium. The CCD results showed that the light intensity and vinasse concentration influenced the amount of biomass produced.